Empleo de bacterias como alternativa de biorremediación en suelos contaminados con mercurio (Hg), Zinc (Zn), aluminio (Al) y cobre (Cu) con empleo de bacterias. - Cedeño Moreira, Angel Virgilio (2022)
8 ABSTRACT Heavy metals are considered one of the most toxic pollutants in the environment because they have harmful effects throughout the entire food chain, due to their persistence and toxicity, with mining being one of the main sources of contamination. The objective of this research is the isolation and characterization of bacteria with potential in the bioremediation of soils contaminated with mercury (Hg), zinc (Zn), aluminum (Al) and copper (Cu). For that, soil samples were collected from three agricultural sites with a history of intensive exploitation, of crops that exhibit high demand for agrochemicals corresponding to the cities of Quevedo